UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI MODEL QUANTUM LEARNING PADA MATA PELAJARAN IPA MATERI PENYESIAIAN DIRI MAKHLUK HIDUP KELAS V SD MUHAMMADIYAH BAUSASRAN - Hendi Dwi Cahyo; Ika Maryani (Universitas Ahmad Dahlan, 2018)
The material taught at this time is increasingly difficult, the way to teach teachers is still conventional, the lack of media and learning facilities, especially in science learning which requires concrete understanding. This study aims to improve motivation and learning outcomes in science lessons through Quantum Learning for fifth grade students at SD Muhammadiyah Bausasran. The subjects in this study were fifth grade students of SD Muhammadiyah Bausasran. The object in this study is the motivation and learning outcomes of science using the Quantum Learning model. Data collection techniques used in the form of observation, tests, and interviews. While the analysis technique uses descriptive quantitative. The research carried out belongs to the type of Class Action Research which consists of two cycles. The criteria for success of action in this study are seen from the increase in motivation and learning outcomes of science using Quantum Learning. The results showed that the activities and learning outcomes of science used Quantum Learning models from cycle I and Cycle II experienced an increase. The results of observation of motivation of students in the first cycle of the first meeting the percentage value of 35.33% reached the criteria of